Untwisting of the DNA helix stimulates the endonuclease activity of Bacillus subtilis Nth at AP sites - Collier, Christopher; Machon, Cristina; Briggs, Geoff S.; Smits, Wiep Klaas; Soultanas, Panos (Oxford University Press, 2011)
Bacterial nucleoid associated proteins play a variety of roles in genome maintenance and dynamics. Their involvement in genome packaging, DNA replication and transcription are well documented but it is still unclear whether they play any specific roles in genome repair. We discovered that untwisting of the DNA double helix by bacterial non-specific DNA binding proteins stimulates the activity of a repair endonuclease of the Nth/MutY family involved in abasic site removal during base excision repair. The essential Bacillus subtilis primosomal gene dnaD, coding for a protein with DNA-untwisting activity, is in the same operon with nth and the promoter activity of this operon is transiently stimulated by H2O2. Consequently, dnaD mRNA levels persist high upon treatment with H2O2 compared to the reduced mRNA levels of the other essential primosomal genes dnaB and dnaI, suggesting that DnaD may play an important role in DNA repair in addition to its essential role in replication initiation. Homologous Nth repair endonucleases are found in nearly all organisms, including humans. Our data have wider implications for DNA repair as they suggest that genome associated proteins that alter the superhelicity of the DNA indirectly facilitate base excision repair mediated by repair endonucleases of the Nth/MutY family.